PENGARUH PEMBERIAN INFORMASI TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG PEMERIKSAAN HIV DI WILAYAH KERJA PUSKESMAS MERAL - Karmia, Karmia; Aryaneta, Yenni (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Human Immunodeficiency Virus (HIV) is known as the top-ranked infectious disease that cause death in human with high probability of mortality and incidence. In fact, HIV requires a long diagnosis as well as therapy. Nowadays, Indonesia becomes the fifth country in Asia with the highest risk of HIV/AIDS. This study aims to determine the impact of information provision to the knowledge and attitudes of pregnant women about HIV examination. This study used a pre-experimental research design with one group pretest-posttest only approach conducted at the working area of Meral Health Center from May to July 2018. The population of this study was all pregnant women and 92 respondents were selected as the sample using quota sampling technique. The result shows the mean score of pregnant mothers’ knowledge level of pre-test 66.37 and post-test 82.22, meanwhile, the mean score for pregnant women’s attitude of pre-test 74.22 and post-test 80.61. On the other hand, statistical test using Paired T-Test shows difference of mean score for pre-test and post-test on knowledge variable is 15.85 with p value = 0.000 (<0.05). Whereas, the difference of mean score between pre-test and post-test for attitude variable is 6.39 with p value = 0.000 (<0.05). In conclusion, there is a significant impact of information assistance on knowledge and attitudes of pregnant women about HIV examination at the Meral Health Centre. Finally, it is hoped that the result of this study can be utilized as evaluation material particularly for reproductive health programs.